New Approaches in Economic Sociology - Beckert, Jens (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The new economic sociology investigates the embeddedness of market activity in economicactors’ political, cultural and social environment. The exploration of markets from a sociological perspective stands at the foreground of this seminar, which is a sequel to Professor Streeck’s winter semester course. For this purpose, four major thematic areas will be highlighted: the cultural and political preconditions for the emergence of markets; the development of valuation in markets; the structuration of markets through institutions and networks; and the social conditions for overcoming possible barriers to market exchange.